As-Syatibi Economic Thinking - Permani, Intan; Iskandar, Iskandar (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2022)
Talking about As-Syatibi's thoughts, where he initiated the concept or thought about the economy in the scope of production, consumption, and distribution. the method used in this research is the library method. This method uses documentaries sourced from literature such as journals, books, papers, and the internet that discuss As-Syatibi's thoughts on Islamic economics. The foundation of As-Syatibi's thoughts on economics refers to the Maqashid Syariah concept whose orientation is to give birth to Maslahah Mursalah. As-Syatibi's thoughts are believed to be very ideal to be implemented in this modern era because the previous thoughts and ideas about economics are deemed to be very irrelevant. Besides being able to answer the challenges of the times, the Maqashid sharia theory which is juxtaposed with this economic thought must also bring about positive changes, especially for Muslim individuals when dealing with and directly involved with the economic activity itself. On the other hand, As-Syatibi divides needs and gives the view that these needs must rely on a priority scale that is matched to each level of need. As for the level of values ??from an economic perspective, As-Syatibi divides them into three, firstly Dharuryah and second, Hajjiyah. And the third is Tahsiniyah. As for the level of values ??from an economic perspective, As-Syatibi divides them into three, firstly Dharuryah and second, Hajjiyah. And the third is Tahsiniyah. As for the level of values ??from an economic perspective, As-Syatibi divides them into three, firstly Dharuryah and second, Hajjiyah. And the third is Tahsiniyah